2014
DOI: 10.1146/annurev-earth-060313-054658
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and Anisotropy of Earth's Inner Core

Abstract: Seismic observations provide strong evidence that Earth's inner core is anisotropic, with larger velocity in the polar than in the equatorial direction. The top 60-80 km of the inner core is isotropic; evidence for an innermost inner core is less compelling. The anisotropy is most likely due to alignment of hcp (hexagonal close-packed) iron crystals, aligned either during solidification or by deformation afterward. The existence of hemispherical variations used to be controversial, but there is now strong evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 168 publications
(241 reference statements)
4
99
2
Order By: Relevance
“…For example, core flow models inverted from the geomagnetic secular variation (Holme 2007) show active Atlantic vs. quiet Pacific hemispheres (Amit and Olson 2006;Aubert et al 2013;Gillet et al 2009;Holme and Olsen 2006;Hulot et al 2002). In addition, the seismic velocity, anisotropy, and attenuation of the inner core exhibit an east-west hemispheric dichotomy (Tanaka and Hamaguchi 1997), although these three seismic properties may sample different parts of the inner core (Deuss 2014;Irving and Deuss 2011). Aubert et al (2008) recovered the observed patterns of the paleomagnetic field and the inner core hemispheric dichotomy in the corresponding time-average quantities of their dynamo model.…”
Section: Relevant Observed Planetary Dynamo Propertiesmentioning
confidence: 75%
“…For example, core flow models inverted from the geomagnetic secular variation (Holme 2007) show active Atlantic vs. quiet Pacific hemispheres (Amit and Olson 2006;Aubert et al 2013;Gillet et al 2009;Holme and Olsen 2006;Hulot et al 2002). In addition, the seismic velocity, anisotropy, and attenuation of the inner core exhibit an east-west hemispheric dichotomy (Tanaka and Hamaguchi 1997), although these three seismic properties may sample different parts of the inner core (Deuss 2014;Irving and Deuss 2011). Aubert et al (2008) recovered the observed patterns of the paleomagnetic field and the inner core hemispheric dichotomy in the corresponding time-average quantities of their dynamo model.…”
Section: Relevant Observed Planetary Dynamo Propertiesmentioning
confidence: 75%
“…Seismological studies of the ICB and its inferred characteristics, such as the density jump between the inner and the outer cores, the shear-wave velocity at the top of the inner core, and scattering of seismic energy from small-scale topography at the inner core surface, are important in elucidating the growth mechanism of the inner core and the source of the geodynamo (Souriau 2007;Sumita and Bergman 2009;Deuss 2014;Tkalčić 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent static compression on iron (11) and iron alloys (12) has highlighted the stability of hexagonal-close-packed (hcp) structure under extreme conditions, whereas previous studies investigated the potential stabilization of double hcp (dhcp) or body-centered cubic (bcc) structures under high pressure and temperature (13)(14)(15)(16)(17). However, having an hcp structure under Earth's inner core conditions is mandatory to explain its anisotropic structure observed by seismology (18,19).…”
mentioning
confidence: 99%